HA/β-TCP Biphasic Calcium Phosphate Ceramics Derived From Butterfish Bones Loaded With Bone Marrow Mesenchymal Stem Cells Promote Osteogenesis - Deng, Kehan; Liu, Zhixiao; Dou, Wenxufe; Cai, Qi; Ma, Wei; Wang, Shaohai (Frontiers in Materials, 2022)
Biphasic calcium phosphate (BCP) containing hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP) is considered the gold standard for bone repair. However, the complex synthesis of BCP restricts the wide application of BCP. In the preliminary work, we proved that the HA/β-TCP BCP ceramic material extracted from fishery waste had a good prospect as a bone replacement graft material for filling bone defects. This study aimed to explore the osteogenesis effect of BCP material derived from butterfish bones in vivo and in vitro. After loading human bone marrow mesenchymal stem cells (hBMSCs) with materials, we used scanning electron microscopy to observe cell adhesion and survival. Western blot analysis was used to detect osteogenic expression in vitro. Micro-computed tomography and hematoxylin–eosin staining were used to detect bone regeneration and material degradation rate in the rat femoral defect model. The results showed that hBMSCs grew well and adhered closely to the material. In vitro, the expression levels of bone formation–related markers ALP and Runx-2 of butterfish bones calcined at 900°C were generally higher than those in the other groups. Notably, in vivo, the osteogenesis ability of butterfish bones calcined at 900°C was almost comparable to that of the most commonly used Bio-Oss in clinical practice and was significantly better than that in the other groups. In summary, the BCP ceramic material derived from butterfish bones had good biocompatibility, osteoconductivity, and osteoinductivity, and had a good application prospect in the field of bone graft substitutes.